2008
DOI: 10.1089/lap.2007.0201
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Duodenoduodenostomy in a Newborn with Situs Inversus Totalis

Abstract: Situs viscerum inversus is a rare embryologic anomaly with a mirror-image transposition of the normal anatomy of organs. The coexistence with the duodenal atresia is extremely rare. This report describes a newborn with duodenal atresia and situs inversus totalis who was managed laparoscopically. According to our knowledge, this is the first report of this type of associated anomaly to be successfully managed by the laparoscopic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Twelve studies were initially identified [3–12, 15, 16] from 2002 to 2014, of which four were case reports [3, 4, 15, 16] and were excluded. Eight studies were included [5–12], of which five focused on LRDA ( n = 67 patients) [5–9], and three were comparative between LRDA ( n = 57 patients) and conventional open repair ( n = 94 patients) [10–12].…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies were initially identified [3–12, 15, 16] from 2002 to 2014, of which four were case reports [3, 4, 15, 16] and were excluded. Eight studies were included [5–12], of which five focused on LRDA ( n = 67 patients) [5–9], and three were comparative between LRDA ( n = 57 patients) and conventional open repair ( n = 94 patients) [10–12].…”
Section: Resultsmentioning
confidence: 99%
“…The spleen was found situated on the right in most of patients as in our patient. [6][7][8][9][10][11] There were 5 cases of polysplenia. In the index case presented, we also found polysplenia on the right, Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Lopez et al [10] " " Asplenia Duodenal atresia ivermark syndrome -" " 14. Habib et al [11] " or at autopsy, but when associated with duodenal atresia it often presents early in the new-born period. [1] On the other hand, patient may present late.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital duodenal obstruction associated with SI is an extremely rare condition, and only about 20 patients have been reported in the literature [2, 6, 7]. In particular, only a few CDS patients associated with SI have ever been reported before [2].…”
Section: Discussionmentioning
confidence: 99%